Formular Development of Oil-in-Water Internal Phase Emulsions from Coconut Oil and Olive Oil Having Antioxidant in the Carotenoid Group from Herbal Extract - บุษบรรณ์, คมสรรค์ (Journal of Health Science of Thailand, 2020)
The purpose of this research was to study the efficiency of antioxidants in the carotenoids group extracted from 10 herbs. Each of 500 grams fresh weight of grinded herb was extracted by 1 liter of hexane: acetone(6:4). The extracts were analyzed to measure the level of total carotenoids and total phenolic contents. It was found that the extracted from Coccinia grandis L. Voigt. and leaf of Pandanus amaryllifolius Roxb. had highest level of total carotenoids: 5.859 and 5.822 ppm, respectively. We found the extracted from the leaf of Cocos nucifera L. var. nucifera. had highest phenolic compounds: 68.833 ppm.. The spectrophotometric assay using DPPH radical shown that Sechium edule Sw extracted had highest antioxidant activity. Its 50% inhibitory concentration (IC50) was 52.481 ppm. With such observations, an emulsion was formulated and prepared by mixing extraction of Coccinia grandis L. Voigt. and leaf of Pandanus amaryllifolius Roxb., and studed its characteristic using coconut oil and olive oil as a comparison for each formula. Chemical and physical property was assessed, including the antioxidant activity, amount of total carotenoids and total phenolic compounds, acid-base, viscosity, size of particle, general appearance, color and smelling at 4, 15, 45 °C, room temperature and heating coolingcycle conditions. The Coccinia grandis L. Voigt. and the leaf of Pandanus amaryllifolius Roxb., formulas which blend of olive oil were found to be more stable than coconut oil, while less stable than standard β-carotene formula. In conditions: 4๐ C, 15๐C and at room temperature, the preparation did not change in physical chemistry; and at heating cooling cycle condition by begin stored at 4๐ C for 48 hours and 45๐C for 48 hours 8 cycles, the two preparations were shown to be physically and chemically stable. Therefore, coconut oil can be use to substitute olive oil in the cosmetic manufacturing; which will increase the value of Thai herbs.